Cardiogenic shock in Taiwan from 2003 to 2017 (CSiT-15 study) - Shih-Chieh Chien (BMC, 2021)
Abstract Background This study investigated temporal trends in the treatment and mortality of patients with cardiogenic shock (CS) in Taiwan in relation to acute myocardial infarction (AMI) accreditation implemented in 2009 and the unavailability of percutaneous ventricular assist devices. Methods Data of patients diagnosed as having CS between January 2003 and December 2017 were collected from Taiwan’s National Health Insurance Research Database. Each case was followed from the date of emergency department arrival or hospital admission for the first incident associated with a CS diagnosis up to a 1-year interval. Measurements included demographics, comorbidities, treatment, mortality, and medical costs. Using an interrupted time-series (ITS) design with multi-level mixed-effects logistic regression model, we assessed the impact of AMI accreditation implementation on the mortality of patients with AMI and CS overall and stratified by the hospital levels. Results In total, 64 049 patients with CS (mean age:70 years; 62% men) were identified. The incidence rate per 105 person-years increased from 17 in 2003 to 25 in 2010 and plateaued thereafter. Average inpatient costs increased from 159 125 points in 2003 to 240 993 points in 2017, indicating a 1.5-fold increase. The intra-aortic balloon pump application rate was approximately 22–25% after 2010 (p = 0.093). Overall, in-hospital, 30-day, and 1-year mortality declined from 60.3%, 63.0%, and 69.3% in 2003 to 47.9%, 50.8% and 59.8% in 2017, respectively. The decline in mortality was more apparent in patients with AMI-CS than in patients with non-AMI-CS. The ITS estimation revealed a 2% lower in-hospital mortality in patients with AMI-CS treated in district hospitals after the AMI accreditation had been implemented for 2 years. Conclusions In Taiwan, the burden of CS has consistently increased due to high patient complexity, advanced therapies, and stable incidence. Mortality declined over time, particularly in patients with AMI-CS, which may be attributable to advancements in AMI therapies and this quality-improving policy.